The effect of liquidity on firm’s performance: Case of Vietnam - Nguyen, Kim Quoc Trung; Nga Phan, Thi Hang; Hang, Nguyen Minh (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
This paper aims to estimate the effect of liquidity on the profitability of firms listed on the Ho Chi Minh City Stock Exchange (HSX) in Vietnam during the COVID-19 outbreak. Using a quantitative research method (the feasible generalized least squares method - FGLS), six factors affecting the firms' performance from 2012 to 2021 are identified: COVID-19, the liquidity ratio, firm age, firm size, tangible assets, and gross domestic product growth. This paper has especially highlighted liquidity's negative and significant effect on firms' performance during the pandemic. Therefore, the study findings indicate that manufacturing firms with high liquidity during COVID-19 lose the opportunity to increase revenue due to funds tied to working capital that cannot be used to support the company's operations under the trade-off theory. Besides, high liquidity also increases the company's opportunity cost, which decreases company profitability. However, the study was conducted in a country with government intervention, political stability, and peace, unlike a country in a period of war and economic difficulties, such as Ukraine. Therefore, the article used a cross-country database for more generalizable results.